As transformações no mundo do trabalho : a produção flexível e suas manifestações na subjetividade do trabalhador - Cordeiro, Luisa Fernandes (2018)
It is proposed, in this study, a reflection on the most contemporary movements of the capitalist mode of production. It is understood the social being as a being that carries objectifications, therefore, composed by subjectivity. An analysis is made as the capitalist mode of production and its gears impact the process of subjectivity formation, especially in the period of flexible production. It is a qualitative research, in which the apprehension of the movement of the real is fundamental. Initially, the fundamentals of the capitalist mode of production are discussed, followed by flexible production and the work category, and being this founder of social being, the first movements that are the key to the dissertation are revealed. Soon after, the social being is discussed, understanding its ontology and the process of the formation of subjectivity, using the categories alienation, commodity fetishism, reification and social praxis. These categories are protoforms for understanding the relationship between social being and the capitalist mode of production. Finally, the object is approximated, with reference to the new international division of labor. At that moment, there is a debate about the conflict between the transformations in the way of generating the work force in flexible production and its impacts on the formation of the subjectivity of the social being in this scenario.